Skipping of Exons by Premature Termination of Transcription and Alternative Splicing within Intron-5 of the Sheep SCF Gene: A Novel Splice Variant - Saravanaperumal, Siva Arumugam (Public Library of Science, 2012)
Stem cell factor (SCF) is a growth factor, essential for haemopoiesis, mast cell development and melanogenesis. In the hematopoietic microenvironment (HM), SCF is produced either as a membrane-bound (−) or soluble (+) forms. Skin expression of SCF stimulates melanocyte migration, proliferation, differentiation, and survival. We report for the first time, a novel mRNA splice variant of SCF from the skin of white merino sheep via cloning and sequencing. Reverse transcriptase (RT)-PCR and molecular prediction revealed two different cDNA products of SCF. Full-length cDNA libraries were enriched by the method of rapid amplification of cDNA ends (RACE-PCR). Nucleotide sequencing and molecular prediction revealed that the primary 1519 base pair (bp) cDNA encodes a precursor protein of 274 amino acids (aa), commonly known as ‘soluble’ isoform. In contrast, the shorter (835 and/or 725 bp) cDNA was found to be a ‘novel’ mRNA splice variant. It contains an open reading frame (ORF) corresponding to a truncated protein of 181 aa (vs 245 aa) with an unique C-terminus lacking the primary proteolytic segment (28 aa) right after the D(175)G site which is necessary to produce ‘soluble’ form of SCF. This alternative splice (AS) variant was explained by the complete nucleotide sequencing of splice junction covering exon 5-intron (5)-exon 6 (948 bp) with a premature termination codon (PTC) whereby exons 6 to 9/10 are skipped (Cassette Exon, CE 6–9/10). We also demonstrated that the Northern blot analysis at transcript level is mediated via an intron-5 splicing event. Our data refine the structure of SCF gene; clarify the presence (+) and/or absence (−) of primary proteolytic-cleavage site specific SCF splice variants. This work provides a basis for understanding the functional role and regulation of SCF in hair follicle melanogenesis in sheep beyond what was known in mice, humans and other mammals.